DIFFERENCES IN DWI IMAGE INFORMATION WITH VARIATION IN B-VALUE IN MRI BRAIN CASES TUMOR - Febriana, Chindi; Susanto, Fani; Fitriana, Lutfatul; Oviyanti, Pradana Nur (LPPM Universitas Awal Bros, 2023)
Diffusion Weighted Imaging (DWI) is a sequence used in brain tumor cases to assess molecular movement (diffusion). DWI is influenced by the selection of the b-value parameter which results in differences in the generated signal. The aim of this study is to determine the differences in b-value variations of 500, 1000, 1500 s/mm2 in brain tumor cases and identify the most optimal variation. This study is a pre-experimental study conducted using a 1.5 Tesla Philips MRI machine at a private hospital in South Jakarta from March to April 2023. The sample consisted of twelve DWI MRI images with different b-value variations. Visual grading analysis was performed by three radiology specialists, and the data were analyzed using the Friedman test in SPSS. The results showed a significant difference in image information based on the use of different b-value variations, with a pvalue of 0.05 (2.36). The use of a b-value of 1000 s/mm had the highest mean rank in the basal ganglia, cerebellum, thalamus, pons, gray matter, and lesions. The difference in image information with b-value variations visualized different brain tumor representations due to increased noise with higher b-values and suboptimal image sharpness with lower b-values due to low signal intensity. The use of b-value variations of 500, 1000, 1500 s/mm2resulted in differences in anatomical image information in sequences DWI MRI brain axial of brain cases tumor due to differences in image noise and signal intensity, with a b-value of 1000 s/mm being the most optimal variation.